Edukasi Personal Hygiene pada Lansia: Personal Hygiene Education for Elderly - Oktarina, Yosi; Misriyani, Veni; Pebriani, Pebriani; Astaria, Wike; Siska, Siska (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Elderly people experience a natural decline in physical, psychological and social functions due to aging factors. This has an impact on the elderly's ability to fulfill personal hygiene. Elderly people with poor personal hygiene can cause various kinds of health problems, both physical and psychological. Therefore, appropriate education is needed to increase the knowledge and behavior of the elderly regarding good personal hygiene. The aim of this service activity is to increase knowledge about good personal hygiene in the elderly. This service activity was carried out on 30 elderly people at PSBAWEP Harapan Mulya. Activity methods include lectures, discussions and demonstrations such as washing hands, brushing teeth, caring for skin, dressing and grooming oneself. The evaluation results showed that elderly knowledge regarding personal hygiene in the good category increased to 83.33%. This shows that there has been an increase in elderly knowledge regarding personal hygiene after being given education.